Mechanical properties of a novel dactyl-inspired green-composite sandwich structures with basalt fiber. (March 2021) - Han, Qigang; Qin, Hanlin; Han, Zhiwu; Li, Lin; Zhang, Wenqiang; Sun, Yanbiao; Shi, Shaoqian
The laminated structural dactyl club of mantis shrimp consisting of the impact and periodic region has been studied, but most researchers only focus on the excellent impact resistance and strength of periodic region through the thickness direction. In this paper, a novel dactyl-inspired basalt fiber-reinforced sandwich-structural composite (BFSC) was manufactured based on two regions of the dactyl club by compression molding process. The BFSC was compared with discontinuous basalt fiber-reinforced composite (DBFC) in mechanical tests of tensile, flexural, compression, hardness and impact. As a result, the strength of tensile, compression, flexural and impact of BFSC were 104 MPa, 112 MPa, 135 MPa and 116 MPa, respectively, which increased to 65.4%, 9.8%, 11.6% and 30.3% than that of DBFC (63.3 MPa, 102 MPa, 121 MPa and 89 MPa). The modulus of tensile and compression of BFSC were 3740 MPa and 971 MPa, respectively, which increased to 58.3% and 38.7% compared with that of DBFC (2362 MPa and 700 MPa). The excellent mechanical properties of BFSC can be attributed to the damage of special sandwich structure, which has failure mechanisms at the microscopic scale, including the crack of resin matrix, fiber breakage, fiber/matrix debonding and delamination. This work presents a novel dactyl-inspired green-composite sandwich structures with basalt fiber. As a lightweight material, it has a wide application in the field of aerospace, high-speed railways and automotive.